2023
DOI: 10.1017/s1742170523000029
|View full text |Cite
|
Sign up to set email alerts
|

Economic trade-offs: analysis of hairy vetch (Vicia villosa) cover crop use in organic tomato (Solanum lycopersicumL.) high tunnel systems across multiple regions

Abstract: High-tunnel (HT) systems have been shown to effectively improve yields, fruit quality and profitability. In order to maximize returns on investment, HTs are frequently planted successively with both winter and summer cash crops and may include >2 crop cycles per year in some climates. The intense cultivation strategies used in HT systems necessitate increased tillage and nutrient demands posing challenges for soil health, environmental quality and long-term economic sustainability, particularly among organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Finally, despite the lack of effect documented for companion planting in our study, this tactic has been understudied relative to grafting for high tunnel management, even though both approaches can be used to generate similar effects with potential synergies among the two. As with grafting, profitability associated with diversifying rotations or integrating nontomato plants in the limited space occupied by high tunnels is a challenge that needs to be overcome before grower adoption occurs (DiGiacomo et al, 2023). It would be helpful to test these approaches using multiple diversification strategies on soils with varying histories of disease and cultivation intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, despite the lack of effect documented for companion planting in our study, this tactic has been understudied relative to grafting for high tunnel management, even though both approaches can be used to generate similar effects with potential synergies among the two. As with grafting, profitability associated with diversifying rotations or integrating nontomato plants in the limited space occupied by high tunnels is a challenge that needs to be overcome before grower adoption occurs (DiGiacomo et al, 2023). It would be helpful to test these approaches using multiple diversification strategies on soils with varying histories of disease and cultivation intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Because the monoculture system did not develop disease pressure and/or reduce yields, it is not surprising that the clover treatment had little to no effect. Field trials of cover crops on tomatoes, in general, show variable effects on crop performance with positive, negative or neutral effects changing across years and sites (Chahal & Van Eerd, 2021; DiGiacomo et al, 2023; Summers et al, 2014). Other authors have demonstrated that positive effects of companion plants depend on the presence of soil pathogens such as Pythium or plant–parasitic nematodes (Hannula et al, 2020; Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study employed partial budgeting techniques for financial analysis (DiGiacomo et al, 2023). The potential partial benefits of the cover crop, N application and preceding residue management changes detailed above included increases in revenue from higher tomato yields, and the sale of crop residue (straw).…”
Section: Financial Effects Of Cover Cropping N Application and Crop R...mentioning
confidence: 99%
“…Some research has employed cost-benefit analysis and financial accounting to assess cover crop viability (Bounaffaa, 2015;DeVincentis et al, 2020;Pratt et al, 2014;Snapp et al, 2005). The financial feasibility of cover crops within a vegetable crop farming system, particularly with field processing tomatoes, have been investigated in the United States (DiGiacomo et al, 2023;Price et al, 2016), and in Canada (Belfry et al, 2017;Chahal et al, 2020), but only for limited timeframes.…”
Section: Introductionmentioning
confidence: 99%